2009
DOI: 10.1007/s10517-010-0784-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Soluble FAS

Abstract: A test system developed by the authors was used to measure serum concentrations of soluble Fas in patients with malignant and benign tumors of different location and morphology. Relationships between soluble Fas levels and the main clinical and morphological characteristics of cancer were evaluated. It is proven that the concentrations and incidence of detection of soluble Fas in the sera of patients with tumors are significantly higher than in normal subjects. No appreciable differences in the concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Similar results were obtained in this study using Panc-1 and SW1990 cells. Several mechanisms have been suggested to play a role in this phenomena, such as the downregulation of Fas (19), the upregulation of FasL (20) and the expression of soluble Fas (21). DcR3, which binds to FasL and inhibits FasLinduced apoptosis, may also play a role in the resistance to FasL/Fas-mediated growth inhibition signals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in this study using Panc-1 and SW1990 cells. Several mechanisms have been suggested to play a role in this phenomena, such as the downregulation of Fas (19), the upregulation of FasL (20) and the expression of soluble Fas (21). DcR3, which binds to FasL and inhibits FasLinduced apoptosis, may also play a role in the resistance to FasL/Fas-mediated growth inhibition signals.…”
Section: Discussionmentioning
confidence: 99%
“…Abbasova et al (2009) found that the sFas median concentration increased with tumor progression, and sFas levels showed significant differences between cases of regional metastases and no metastases in colorectal cancer. In the present study, the sFas levels before and after treatment in those with LAURC were higher than those in healthy controls.…”
Section: Discussionmentioning
confidence: 89%
“…This shorter product is soluble and inhibits FAS‐mediated cell death, presumably by binding competition for the FAS ligand . High levels of serum soluble FAS have been reported in cancer patients, including ovarian cancer . However, in vitro, in the conditioned medium of primary ovarian cancer cells, the levels of soluble FAS were minimal and not significantly different from those of normal ovarian cells .…”
Section: Discussionmentioning
confidence: 99%
“…62 High levels of serum soluble FAS have been reported in cancer patients, including ovarian cancer. [63][64][65] However, in vitro, in the conditioned medium of primary ovarian cancer cells, the levels of soluble FAS were minimal and not significantly different from those of normal ovarian cells. 57 Similarly, we have demonstrated that soluble FAS protein was undetectable in OVCAR-3 cells.…”
Section: Figurementioning
confidence: 99%